Teaching of discrete mathematics for first course students of Faculty of Electronics in VGTU - Aleksandras Krylovas; Olga Suboč (Lietuvos Matematikos Rinkinys)
In this article we present methodics of teaching discrete mathematics for first course students of Faculty of Electronics in VGTU. We present analysis of marks in course and separate groups, relaitionship between results of two tests.